Social-emotional aspects in adolescents with mathematical talent living in Lima - Yucra Camposano, Jennifer (2018)
A descriptive and comparative study is conducted in order to compare the self-esteem and social skills in adolescents with mathematical talent according to their sex. The participants were 16 men and 13 women, between the ages of 12 and 16 years old, living in Lima and coming from the capital and provinces. The Self-Esteem Inventory (SEI) to children and adolescents by Coopersmith and the List of Checkup of Social Abilities by Goldstein were used as instruments. The results in general, show low levels of self-esteem and average level of social skills in men and women. Women present higher expectations in the terms of study and they are more satisfied with their performance in mathematic. Also, they have skills  developed in the defend of their rights, negotiate, avoid physical and/or verbal fights. As well as to establish goals, solve problems according to the importance, take decisions and the skills of focus in a task.